L'ús de les llengües minoritàries en les xarxes socials: el valencià en Twitter. - Tölke, Vanessa (Zeitschrift für Katalanistik, 2015)
This article's aim is to analyze the use of Valencian in the social network Twitter. It addresses the issue of whether Twitter can contribute to the preservation of minority languages such as Valencian and can thus be regarded as a support for the normalization of the language. In this context an attempt is made to define communication within Twitter and to establish whether the language used in the network is characterized as spoken or written language. These questions are explored via a quantitative approach, based on a corpus of tweets in Valencian. The article further examines to what extent Twitter users follow the official Valencian language norm, represented by the Acadèmia Valenciana de la Llengua. The analysis reveals that Valencian is the most commonly used language amongst the speakers of the corpus, which could serve as evidence for the normalized use of Valencian at least in a specific region of the Valencian Community, the Marina Alta. Additionally, the hypothesis that communication in Twitter is composed of a hybrid of spoken and written language can be confirmed.